PENGEMBANGAN FORMULA ENTERAL “NUTRIGRAIN” BERBASIS TEPUNG MULTIGRAIN BAGI PASIEN DIABETES MELITUS - Meila Asty, Milla; Gumilar, Mulus; Isdiany, Nitta; Moviana, Yenny (Jurusan Gizi Poltekkes Kemenkes Bandung, 2025)
Enteral feeding is a nutritional therapy given to unconscious patients or dysphagia. Nutrigrain is a powder enteral formula based on multigrain flour (soybean, mung bean, brown rice, hanjeli, and sesame) as a source of protein with complex carbohydrates, antioxidants, and fiber to control blood sugar. The purpose of this study was to determine the effect of legume (soybean and mung bean) and cereal (brown rice, hanjeli, and sesame) formulations on the quality of enteral formula. The design of this study was an experiment involving 30 moderately trained panelists on organoleptic testing. The data normality test used Shapiro-Wilk, and the result was that the data was not normally distributed, so the data analysis used the Kruskal-Wallis test. Statistical testing shows that there was an effect of legume and cereal formulations on the quality of enteral formula from the aspects of taste (p=0.002), aroma (p=0.020), and consistency (p=0.023). The aspects of color (p=0.06) and overall (p=0.068) showed no effect of different formulations. The second formula (50% legumes: 50% cereals) was the best formula with an average hedonic score of 6.0. The laboratory test results show energy 268 kcal, calorie density of 1,3 kcal/ml, protein 12,19 grams, fat 6,97 grams, carbohydrates 39,18 grams, fiber 5,19 grams, and antioxidant activity (IC50) 1609,11 ppm per serving. The flow-ability test result is 0,10 ml/second. Nutrigrain product price per serving size is Rp. 13,873,-. Microbiological testing and product shelf life in the laboratory are recommended and need a reformulation to increase antioxidant activity. Key words: diabetes mellitus, enteral formula, multigrain, antioxidant activity